Colored asphalt cohesive force testing device and testing method
By designing a color asphalt viscosity test device to simulate environmental external forces and natural aging conditions, the problem of decreasing viscosity of color asphalt is solved, and a more accurate viscosity evaluation is achieved, ensuring the performance and safety of the material.
Patent Information
- Application Number
- CN202411465980.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-14
AI Technical Summary
Colored asphalt will age under long-term exposure to complex environmental conditions, resulting in a decrease in adhesion and increasing the risk of road surface diseases. It is difficult for the existing technology to effectively evaluate its adhesion.
Design a color asphalt viscosity testing device, including test container, rotating shaft, drive parts, tire simulation parts and environmental simulation parts. By simulating the environmental external force and the action force of the wheel, combined with temperature control and aging devices, it simulates the aging conditions of the natural environment. .
By simulating different environmental conditions, the viscosity characteristics of colored asphalt can be more comprehensively evaluated, the accuracy of viscosity evaluation can be improved, and the performance and safety of colored asphalt materials in actual applications can be ensured.
Smart Images

Figure CN119438067A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of pavement material testing devices, and in particular to a colored asphalt cohesion testing device and a testing method. Background Art
[0002] Colored asphalt, as a special pavement material, will gradually undergo physical and chemical changes when exposed to complex and changing external environmental conditions for a long time, such as extreme high temperatures, strong ultraviolet light, frequent rain and continuous vehicle rolling. This process is called "aging". This will lead to a significant decrease in the adhesion of colored asphalt, peeling between the colored asphalt layer and the aggregate, and increase the risk of pavement diseases such as cracks and potholes, further affecting the safety and service life of the road.
[0003] Therefore, how to ensure that colored asphalt has good cohesion is the key to preventing road damage. Therefore, this application studies a colored asphalt cohesion test device to simulate the destruction process of colored asphalt under environmental external forces and wheel forces, and improve the accuracy of colored asphalt cohesion evaluation. Summary of the invention
[0004] In order to improve the accuracy of colored asphalt cohesion evaluation.
[0005] On the one hand, the present application provides a colored asphalt cohesion test device, which adopts the following technical solution:
[0006] A colored asphalt cohesion test device comprises a test container, a rotating shaft, a driving member, a tire simulation member and an environmental simulation member, wherein the rotating shaft is rotatably connected to the center of the test container, the driving member drives the rotating shaft to drive the test container to rotate, a plurality of tire simulation members are detachably arranged along the inner wall of the test container, and the environmental simulation member is placed in the test container; a temperature control system is also provided, and the temperature control system is used to control the temperature inside the test container.
[0007] Optionally, the tire simulation is divided into a first part and a second part, the first part is a cylindrical structure, the second part is a conical structure, the diameter of the first part is 10 mm, the bottom diameter of the second part is the same as the diameter of the first part, and the total height of the first part and the second part is 20 mm.
[0008] Optionally, the tire simulation pieces are arranged in an array, and the spacing between adjacent tire simulation pieces is 20 mm.
[0009] Optionally, the outer layer of the tire simulation is wrapped with chloroprene rubber, and the hardness of the chloroprene rubber HV≥450.
[0010] Optionally, the environmental simulation component is a steel ball.
[0011] On the other hand, the present application provides a method for testing the cohesion of colored asphalt, which adopts the following technical solution:
[0012] A method for testing the cohesion of colored asphalt comprises the following steps:
[0013] S1: First, the colored asphalt sample was aged at 163°C for 85 min, and then the aged colored asphalt sample was passed through an aging device to simulate medium- and long-term aging;
[0014] S2: The aged colored asphalt sample is mixed with aggregate according to the gradation required for pavement construction and compacted 50 times on both sides to form a standard Marshall specimen. After cooling, the weight is m 1 ;
[0015] S3: Soak the specimen in 60℃ water for 48h;
[0016] S4: Place the saturated test piece into the above-mentioned colored asphalt cohesion test device, control the temperature to 60°C, and drive the rotating shaft to drive the test container to rotate. After 10,000 rotations, stop. Take out the larger test piece after wear and tear, and dry it at 60°C to constant weight. Record the weight as m 2 ;
[0017] S5: The m obtained in step S2 and step S4 is 1 and m 2 , calculate the completeness rate as follows:
[0018]
[0019] S6: The cohesion of colored asphalt is evaluated by the integrity rate, and the four levels of integrity rate of 95%, 90%, 85% and 80% are respectively judged as level one, level two, level three and level four.
[0020] Optionally, the aging device includes an aging container, the aging container is provided with an inflation valve and an exhaust valve, a xenon lamp is arranged inside, and a temperature control system is provided for controlling the temperature inside the aging container.
[0021] Optionally, in step S1, gas is filled into the inflation valve with a pressure of 2.1 MPa; the color temperature of the xenon lamp is 6000K, the temperature control system controls the temperature to 110°C, and the aging time is 22h.
[0022] In summary, this application includes the following beneficial technical effects:
[0023] 1. The tire simulator simulates the tire, and the environmental simulator simulates the process of the road surface being hit by other heavy objects. By simulating different environmental conditions, the cohesion characteristics can be evaluated more comprehensively, thereby improving the accuracy of the cohesion evaluation of colored asphalt, which helps to ensure the performance and safety of colored asphalt materials in practical applications;
[0024] 2. The design of the tire simulation part can be used more comprehensively to simulate the contact between the colored asphalt and the outer wall structure of the tire with different shapes. The second part is more likely to peel off the colored asphalt mixture with insufficient adhesion during the centrifugal rotation process. This design not only takes into account the contact between the colored asphalt and the rigid boundary, but also takes into account the deformation and flow characteristics of the colored asphalt under pressure or shear force, which helps to more accurately evaluate the cohesion characteristics of the colored asphalt, as well as its performance and safety under different conditions; chloroprene rubber is a tire material, and its hardness is consistent with that of the tire, so that the damage of the tire to the colored asphalt can be simulated more accurately;
[0025] 3. By filling with gas, xenon lamp and temperature control, the aging of colored asphalt under air, light and temperature conditions is simulated at the same time, so that the aging conditions of the natural environment can be simulated more accurately, thereby better ensuring the accuracy of the integrity rate in the colored asphalt test. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a cross-sectional schematic diagram of a colored asphalt cohesion test device according to an embodiment of the present application;
[0027] Figure 2 It is a cross-sectional schematic diagram of the aging device in the colored asphalt cohesion testing method according to the embodiment of the present application.
[0028] Figure numerals: 1. test container; 2. rotating shaft; 3. driving member; 4. tire simulation member; 5. environmental simulation member; 6. mounting plate; 7. aging container; 71. cover body; 72. shell; 8. inflation valve; 9. deflation valve; 10. xenon lamp; 11. tray. DETAILED DESCRIPTION
[0029] The following is combined with Figure 1-2 This application is described in further detail.
[0030] The present application embodiment discloses a color asphalt cohesion test device. Figure 1The colored asphalt cohesion test device includes a test container 1, a rotating shaft 2, a driving member 3, a tire simulation member 4 and an environmental simulation member 5. The test container 1 of this embodiment is a cylindrical structure with an inner height of 110 mm and an inner diameter of 600 mm. A shell (not shown in the figure) is also installed outside the test container 1 of this embodiment. The driving member 3 is a motor. The test container 1 and the motor are both arranged in the shell. The shell is a prior art and is not described here. The rotating shaft 2 is connected to the center of the test container 1. The driving member 3 drives the rotating shaft 2 to drive the test container 1 to rotate and drive the colored asphalt to perform centrifugal motion. Several tire simulation members 4 are spaced and detachably arranged along the inner side wall of the test container 1. The tire simulation member 4 is used to simulate the outer surface of the tire. The environmental simulation member 5 is placed in the test container 1 to simulate the impact of other objects on the road surface. A temperature control system is also provided, and the temperature control system is used to control the temperature inside the test container 1. This embodiment uses the colored asphalt disclosed in the announcement number CN113136110B as a sample for testing. During the test, the colored asphalt sample is aged and then mixed with aggregate, and the double-sided compaction is used 50 times to form a standard Marshall specimen according to the grading required for pavement construction. The specimen is then placed in the test container 1 for a simulation experiment, which can more accurately simulate the actual situation when the colored asphalt is used on the road, and better ensure the accuracy of the evaluation.
[0031] In some embodiments, the tire simulation part 4 is divided into a first part and a second part, both of which are made of hard materials, the first part is a cylindrical structure, and the second part is a conical structure. In this embodiment, the first part and the second part are integrally formed. The diameter of the first part is 10 mm, the bottom diameter of the second part is the same as the diameter of the first part, and the total height of the first part and the second part is 20 mm. This makes it possible to better simulate the force of the outer shape of the tire on the road surface, so that the color asphalt cohesion test can be more accurate.
[0032] In some embodiments, the tire simulation parts 4 are arranged in an array, and the spacing between adjacent tire simulation parts 4 is 20 mm. In addition, a mounting plate 6 is provided in this embodiment, and the tire simulation parts 4 are mounted in an array on the mounting plate 6. The mounting plate 6 is made of a hard material such as stainless steel or aluminum alloy, and can be bent to conform to the internal shape of the test container 1. The mounting plate 6 is fixed to the inner wall surface of the test container 1 by a detachable method such as snap-fitting or screwing. After one or several tests, the tire simulation parts 4 need to be replaced. Only the mounting plate 6 needs to be disassembled to remove the tire simulation parts 4, and then a new mounting plate 6 (mounting plate 6 provided with the tire simulation parts 4) can be replaced, so that the subsequent test results can be more accurate.
[0033] In some embodiments, the outer layer of the tire simulation part 4 is wrapped with chloroprene rubber, and the hardness of the chloroprene rubber is HV≥450. In this embodiment, the chloroprene rubber is the tire material, and the hardness is consistent with the tire hardness, so that the wear of the tire on the road surface can be simulated more realistically and accurately, so that the result is more accurate.
[0034] In some embodiments, the environment simulation member 5 is a steel ball. This embodiment uses a steel ball with a diameter of 10 mm, and 1000 g is placed in each test.
[0035] The implementation principle of a colored asphalt cohesion testing device in an embodiment of the present application is: the tire simulation part 4 is used to simulate the tire, and the environmental simulation part 5 is used to simulate the process of the road surface being hit by other heavy objects. By simulating different environmental conditions, the cohesion characteristics can be evaluated more comprehensively, thereby improving the accuracy of the colored asphalt cohesion evaluation, which helps to ensure the performance and safety of the colored asphalt material in practical applications.
[0036] The embodiment of the present application also discloses a method for testing the cohesion of colored asphalt.
[0037] The method for testing the cohesion of colored asphalt includes the following steps:
[0038] S1: First, place the colored asphalt sample in a rotary thin film oven at 163°C for 85 minutes, and then take 100g of the aged colored asphalt sample through an aging device to simulate medium- and long-term aging.
[0039] In this embodiment, the aging device includes an aging container 7. The aging container 7 is made of a material that is resistant to high pressure and high temperature. The aging container 7 includes a cover 71 and a shell 72. The cover 71 and the shell 72 are sealed when they are closed. The aging container 7 is provided with an air filling valve 8 and an air release valve 9, and a xenon lamp 10 is arranged inside. The xenon lamp 10 is a short arc xenon lamp 10. Multiple xenon lamps 10 are arranged on the inner wall of the aging container 7 to ensure that the colored asphalt sample can be fully irradiated. A temperature control system is also provided to control the temperature in the aging container 7. A surface area of 200cm is also provided. 2 The tray 11 is a cylindrical disc structure. The colored asphalt samples are placed on the tray 11. The tray 11 has multiple layers. The multi-layer tray 11 can increase the test efficiency. The colored asphalt samples are placed on trays 11 of different layers, and the spacing between each layer of the tray 11 is large enough to ensure that the xenon lamp 10 can fully illuminate the colored asphalt of each layer, so that the colored asphalt is fully in contact with the light of the xenon lamp 10.
[0040] In step S1, gas is charged from the inflation valve 8, and the pressure value is 2.1MPa; the color temperature of the xenon lamp 10 is 6000K, with continuous spectrum characteristics, and the light color is close to sunlight, which can better simulate the irradiation of sunlight on the road surface. The temperature control system controls the temperature to 110℃ and the aging time to 22h. The three conditions of xenon lamp 10, temperature and pressure can well simulate the aging conditions of the natural environment, so that more accurate test data can be obtained.
[0041] S2: The aged colored asphalt sample is mixed with aggregate according to the gradation required for pavement construction and compacted 50 times on both sides to form a standard Marshall specimen. After cooling, the weight is m 1 ;
[0042] S3: Soak the specimen in 60℃ water for 48h;
[0043] S4: Place the saturated test piece into the above-mentioned colored asphalt cohesion test device. This embodiment uses a steel ball with a diameter of 10 mm, and 1000 g is placed in each test.
[0044] The temperature is controlled at 60°C. The driving member 3 drives the rotating shaft 2 to drive the test container 1 to rotate. After rotating for 10,000 times, the larger test block after wear is taken out. In this embodiment, the largest test block is taken out and dried in a 60°C oven to constant weight. The weight is recorded as m 2 ;
[0045] S5: The m obtained in step S2 and step S4 is 1 and m 2 , calculate the completeness rate as follows:
[0046]
[0047] S6: The cohesion of colored asphalt is evaluated by the integrity rate, and the four levels of integrity rate of 95%, 90%, 85% and 80% are respectively judged as level one, level two, level three and level four.
[0048] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A colored asphalt cohesion test device, characterized in that: The invention comprises a test container, a rotating shaft, a driving member, a tire simulation member and an environmental simulation member. The rotating shaft is rotatably connected to the center of the test container. The driving member drives the rotating shaft to drive the test container to rotate. A plurality of tire simulation members are detachably arranged along the inner wall of the test container. The environmental simulation member is placed in the test container. A temperature control system is also provided. The temperature control system is used to control the temperature inside the test container.
2. A colored asphalt cohesion test device according to claim 1, characterized in that: The tire simulation part is divided into a first part and a second part, the first part is a cylindrical structure, the second part is a conical structure, the diameter of the first part is 10 mm, the bottom diameter of the second part is the same as the diameter of the first part, and the total height of the first part and the second part is 20 mm.
3. A colored asphalt cohesion test device according to claim 1 or 2, characterized in that: The tire simulation pieces are arranged in an array, and the spacing between adjacent tire simulation pieces is 20 mm.
4. A colored asphalt cohesion test device according to claim 1, characterized in that: The outer layer of the tire simulation part is wrapped with chloroprene rubber, and the hardness of the chloroprene rubber is HV≥450.
5. The color asphalt cohesion test device according to claim 1, characterized in that: The environmental simulation part is a steel ball.
6. A method for testing the cohesion of colored asphalt, characterized in that: The following steps are involved: S1: First, the colored asphalt sample was aged at 163°C for 85 min, and then the aged colored asphalt sample was passed through an aging device to simulate medium- and long-term aging; S2: The aged colored asphalt sample is mixed with aggregate according to the gradation required for pavement construction and compacted 50 times on both sides to form a standard Marshall specimen. After cooling, the weight is m1; S3: Soak the specimen in 60℃ water for 48h; S4: Place the saturated test piece into the above-mentioned colored asphalt cohesion test device, control the temperature to 60°C, and drive the rotating shaft to drive the test container to rotate. Stop after 10,000 rotations. Take out the larger test piece after wear and dry it at 60°C to constant weight. Record the weight as m2; S5: Calculate the completeness rate by using m1 and m2 obtained in step S2 and step S4 according to the following formula: S6: The cohesion of colored asphalt is evaluated by the integrity rate, and the four levels of integrity rate of 95%, 90%, 85% and 80% are respectively judged as level one, level two, level three and level four.
7. A method for testing the cohesion of colored asphalt according to claim 6, characterized in that: The aging device comprises an aging container, the aging container is provided with an air filling valve and an air release valve, a xenon lamp is arranged inside, and a temperature control system is arranged for controlling the temperature inside the aging container.
8. A method for testing the cohesion of colored asphalt according to claim 7, characterized in that: In step S1, gas is charged into the gas charging valve at a pressure of 2.1 MPa; the color temperature of the xenon lamp is 6000K, the temperature of the temperature control system is controlled at 110°C, and the aging time is 22h.
Citation Information
Patent Citations
A colored asphalt binder and its preparation method
CN113136110B